Re-Directing African Cocoa Bean Export Performance in the Face of Global Cocoa Trade - Sadiq, S.; P., Singh; P., Singh; M., Ahmad; M., Ahmad (Jordan Journal of Economic Sciences, 2020)
The performance of African cocoa in the global market has not been impressive with ample an gain been lost despite its exportation lead position in the world. It is against this background that he present research looks into the possibility of re-directing the African cocoa export in the global market in order to increase its gain due to its position as the largest exporter of the product in the world. Annual time series data which covered cocoa export and import both in physical and monetary terms for the World, Africa, other continents and macro-economic indicators sourced from the FAO and UNCTAD data banks spanning from 1991 to 2017 were used. The data were analyzed using both descriptive and inferential statistics. Evidenced showed that African cocoa has competitive advantage and its geographical trade concentration can be increase if the continent increase its current export by 41.73%, thus spurring an export value gain of 40.82% over the current average export value recorded for the study period. Furthermore, it was observed that the African cocoa exporters respond to any innovation that induced deviation from the equilibrium in a manner that the current export quantity of cocoa will converge towards the equilibrium. The major factor affecting export decision cum export performance of African cocoa in the global cocoa trade market is the price factor. Therefore, the regional bloc organization (AU) and the major exporting economies should checkmate the oligopsony power of the importing countries through pricing efficiency. Also, there is need to enhance the quality of the product.